A Molecular Investigation of Human Self-Domestication. Issue 4 (April 2020) - Wilkins, Adam S.
Abstract : The question of whether human beings are like domesticated animals in their behavior has been simultaneously intriguing, hard to define precisely, and seemingly resistant to any kind of scientific test. A recent paper by Zanella et al . reports a molecular-genetic approach to it and provides a provisional 'yes'.